2016
DOI: 10.1089/gtmb.2016.0113
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of Hereditary Breast Cancer Genetic Services: Are Changes Reflected in the Knowledge and Clinical Practices of Florida Providers?

Abstract: Results highlight the need to identify whether variability in hereditary cancer service delivery impacts patient outcomes. Findings also reveal opportunities to facilitate ongoing outreach and education.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 30 publications
0
9
0
Order By: Relevance
“…34,35,38,39,41,42,44,[47][48][49][50]55,58 In seven studies, objective knowledge was assessed with a survey utilizing a scale or test to measure accurate understanding of basic genetic principles, clinical practice guidelines, and/or features of hereditary cancer syndromes. 35,38,39,42,47,48,50 In the other six studies, case scenarios or standardized patients were used to measure PCPs' abilities to identify high-risk patients and appropriate genetic testing situations. 32,34,41,44,49,55 Aside from articles reporting on the same sample, 38,48 there was no overlap in measures.…”
Section: Knowledge Of Genetic Tests For Cancer Riskmentioning
confidence: 99%
See 4 more Smart Citations
“…34,35,38,39,41,42,44,[47][48][49][50]55,58 In seven studies, objective knowledge was assessed with a survey utilizing a scale or test to measure accurate understanding of basic genetic principles, clinical practice guidelines, and/or features of hereditary cancer syndromes. 35,38,39,42,47,48,50 In the other six studies, case scenarios or standardized patients were used to measure PCPs' abilities to identify high-risk patients and appropriate genetic testing situations. 32,34,41,44,49,55 Aside from articles reporting on the same sample, 38,48 there was no overlap in measures.…”
Section: Knowledge Of Genetic Tests For Cancer Riskmentioning
confidence: 99%
“…42 In addition, three studies examined objective knowledge pertaining to legal genetic discrimination protections. 39,44,53 Knowledge in this domain was concluded to be suboptimal; for instance, in a cross-sectional survey of 1120 family practitioners and internists, 9% had accurate knowledge about legal insurance protections related to genetic test results. 53 Ten studies examined PCPs' self-reported subjective or perceived knowledge.…”
Section: Knowledge Of Genetic Tests For Cancer Riskmentioning
confidence: 99%
See 3 more Smart Citations